Prothrombin Complex Concentrate in Liver Transplant Surgery: Correction of Therapeutic Anticoagulation and the Coagulopathy of End-Stage Liver Disease: Case Series - Marshall, Scarlett V.; Noble, Jordan; Flores, Antolin S. (Frontiers in Pharmacology, 2020)
Suggested treatment for active bleeding or invasive procedure prophylaxis has been described in the setting of end-stage liver disease (ESLD) in patients not receiving anticoagulation, and has included fresh frozen plasma (FFP), prothrombin complex concentrates (PCC), platelets, and cryoprecipitate. Today, the therapy for pharmacologically anticoagulated patients with ESLD presenting for liver transplant surgery remains controversial, poorly studied, and physician-dependent. We observed a variety of treatments administered at initiation of liver transplantation to correct acquired coagulopathy at our leading transplant center and present these cases. Three patients receiving preoperative therapeutic anticoagulation with warfarin for acute deep venous thrombosis and/or atrial fibrillation were transfused PCC, FFP, and/or cryoprecipitate for liver or liver-kidney transplant surgery. No thrombotic complications occurred, and one patient required reoperation for hemorrhage. We report data from these cases including estimated blood loss, presence of complications, duration of ICU stay, and length of hospitalization. Perioperative orthotopic liver transplant hematologic management and a review of relevant literature is presented.